2011
DOI: 10.1016/j.psc.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuroimaging in Geriatric Depression

Abstract: Synopsis Abnormalities in specific cerebral networks likely confer vulnerability that increases the susceptibility for development of geriatric depression and impact the course of symptoms. Functional neuroimaging enables the in vivo identification of alterations in cerebral function that not only characterize disease vulnerability, but also may contribute to variability in depressive symptoms and antidepressant response. Judicious use of functional neuroimaging tools can advance pathophysiological models of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 154 publications
0
9
0
2
Order By: Relevance
“…In these patients, binding potential in the anterior cingulate measured with PET has been found to be decreased when compared to healthy controls (Santhosh et al 2009). Reduced 5-HT 2A binding in frontal, occipital, temporal and cingulate cortices was found in patients suffering from depression (Gunning and Smith 2011;Messa et al 2003), while after recovery from anorexia nervosa a reduction was observed in the mesial temporal cortex and cingulate cortex (Frank et al 2002). In studies by G. Knudsen and co-workers, OCD has been linked to elevated levels of 5-HT 2A binding in the caudate nucleus (Adams et al 2005), as well as to Tourette's syndrome which was associated with increased binding in orbitofrontal cortex, anterior cingulate, frontal cortex and other regions of the brain (Haugbol et al 2007).…”
Section: -Ht 2amentioning
confidence: 97%
“…In these patients, binding potential in the anterior cingulate measured with PET has been found to be decreased when compared to healthy controls (Santhosh et al 2009). Reduced 5-HT 2A binding in frontal, occipital, temporal and cingulate cortices was found in patients suffering from depression (Gunning and Smith 2011;Messa et al 2003), while after recovery from anorexia nervosa a reduction was observed in the mesial temporal cortex and cingulate cortex (Frank et al 2002). In studies by G. Knudsen and co-workers, OCD has been linked to elevated levels of 5-HT 2A binding in the caudate nucleus (Adams et al 2005), as well as to Tourette's syndrome which was associated with increased binding in orbitofrontal cortex, anterior cingulate, frontal cortex and other regions of the brain (Haugbol et al 2007).…”
Section: -Ht 2amentioning
confidence: 97%
“…Their activity reduces with antidepressant treatment. 44 Overall, functional neuroimaging studies in late-life depression reveal a pattern of abnormal activation of frontolimbic regions, generally characterized by hypoactivation of specific dorsal cortical regions, including the DLPFC and the dorsal ACC, and hyperactivation of some limbic structures, such as the amygdala. 44 However, the bulk of the existent data are from midlife or mixedage depression studies; it is possible that as more data become available, a different pattern may emerge in late life.…”
Section: Contributors To Elder Depressionmentioning
confidence: 99%
“…The prefrontal cortex, cingulate cortex, amygdala, hippocampus, and hypothalamus are some of the areas thought to be of critical importance. Evidence suggests that each of these brain areas can serve as functional nodes, 7 are necessary to the processing of emotions, and can be impaired in depression; hence are referred to here as a “neural network underlying mood” or “mood network”. Specifically, the prefrontal and cingulate cortices are implicated in the control and regulation of subcortical limbic brain regions, including the amygdala, hippocampus and hypothalamus 8 , and together are associated with emotional expression and experience.…”
Section: Depression a Complex Biological Diseasementioning
confidence: 99%